2020
DOI: 10.1177/0194599820912030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sevoflurane‐Based Anesthesia versus Total Intravenous Anesthesia on Intraoperative Neuromonitoring during Thyroidectomy

Abstract: Objective To examine the influence of sevoflurane-based combined intravenous and inhaled anesthesia versus propofol-based total intravenous anesthesia (TIVA) on intraoperative neuromonitoring (IONM) during thyroidectomy. Study Design A randomized controlled trial. Setting The present study was conducted in a tertiary hospital. Subjects and Methods Forty patients were randomly assigned to a sevoflurane-based combined intravenous and inhalation group (group S) or a propofol-based total intravenous group (group P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
2
0
11
Order By: Relevance
“…Após a tireoidectomia total, o paciente precisará de terapia de reposição hormonal para manter os níveis adequados de hormônios tireoidianos no corpo 5,6,8 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Após a tireoidectomia total, o paciente precisará de terapia de reposição hormonal para manter os níveis adequados de hormônios tireoidianos no corpo 5,6,8 .…”
Section: Resultsunclassified
“…Existem diferentes tipos de tireoidectomia: tireoidectomia total, que é a remoção completa da glândula tireoide; lobectomia tireoidiana, que é a remoção de um dos lobos da tireoide; tireoidectomia subtotal, que é a remoção de parte da tireoide, deixando uma pequena porção da glândula; e isthmusectomia, que é a remoção do istmo da tireoide, a porção que conecta os dois lobos da glândula 7,8,9 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The second reason for the difference is the application of TIVA rather than sevoflurane for maintenance of anesthesia in the present study. The enhancement and prolongation of the effect of NMBAs that occurs with inhaled agents were consequently avoided (24)(25)(26). Therefore, we recommend cisatracurium at an optimal dosage of 2× ED 95 (0.1 mg/kg) for intubation of patients undergoing thyroidectomy with IONM.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this concept, a recent study investigating IONM quality during thyroid surgery reported that time to first satisfactory EMG signal in patients who were administered inhaled anesthetic agent was longer by about 4 minutes compared to those who received TIVA 36) .…”
Section: Selecting Maintenance Anesthetic Agentsmentioning
confidence: 90%